Efektivitas Kelas Kesenian Dalam Meningkatkan Kemampuan Kreatif Anak Usia 4-6 Tahun Di Calistung Nurul Islam Desa Cicau - Rismawati; Meia Salina Lestari; Putri Dela Asyfa; Robi Sutana Putra; Hermawan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Youth training assumes a critical part in cultivating youngsters' creativity. This study evaluates the impact of art classes on enhancing creative abilities in children at Calistung Nurul Islam. The approach involved conducting art sessions, including mosaic art and creating piggy banks from plastic bottles, for children aged 4-6 years. The study found that these art classes significantly boosted children's creativity, as evidenced by their enthusiasm and imaginative exploration. Observations from classes I and II indicated that art activities led to noticeable improvements in creativity, as reflected in pre- and post-class assessments. The research concluded that art classes effectively enhance early childhood creativity, with significant gains observed in children following activities like mosaic art and plastic bottle piggy banks with a percentage of 26.02%, and after the art class in class I experienced a very large increase of 50.36%. In class II, the ability of children's creativity through mosaic art classes and making piggy banks from plastic bottles, experienced an increase and a very good increase in the percentage of 82.00%. Art classes are also effective for stimulating children's motor skills and are useful for increasing children's creativity.